Ableism’s Impact on Body and Identity in Indra Sinha’s Animal’s People - Mary Job T; Christine Ann Thomas; G S Prakasha (Asiatic: IIUM Journal of English Language and Literature, 2025)
This study explores the link between ableism and identity formation through the discourse analysis of Indra Sinha’s Animal’s People (2007). Set against the backdrop of a post-industrial disaster, the Bhopal gas tragedy in an Indian metropolis, the novel provides a powerful narrative about the marginalised. By analysing the social perceptions and structures that define ability, normalcy, and physical beauty, the study investigates how societal norms and cultural attitudes frame the protagonist’s experiences of exclusion and identity crisis. The study further investigates how the novel critiques the broader social and cultural dimensions of ableism in post-colonial contexts, revealing the intersection of power, disability, and identity in the social fabric of Asian societies. Social constructionist perspectives provide a framework for comprehending the social construction of disability, stigma, othering of disabled bodies, and cultural norms of beauty, normalcy, ability, and identity. Subjective and objective realities are discussed around the character, Animal. The study findings reveal the profound personal consequence of ableism on the self-image, body image, and self-perception of individuals with disabilities, the dehumanisation, marginalisation, and ultimately, an identity crisis of disabled individuals.